Influence of stocking density on growth, production and survival of Macrobrachium rosenbergii (de Man) in a monoculture grow-out pond - Nagarathinam, N; Kumar, J Stephen Sampath; Sundararaj, V (Indian Journal of Fisheries, 2011)
Growth and production characteristics of Macrobrachium rosenbergii stocked attwo densities were examined. Prawn juveniles (0.78±0.54 g) were reared for 180days in 0.0014 ha tanks at two stocking densities (5/m2 and 10/m2) individually.The culture tanks were manured with cowdung and inorganic fertilizers and asupplementary feed of 22% crude protein was given to the prawns. The resultsindicated that at low stocking density (5/m2) the growth and survival were higher.Prawns attained a final mean body weight of 31.32±21.5 g and 28.38±14.23 g inlow and higher stocking densities, respectively. The estimated productions were984.34 and 1,662.26 kg/ha per crop, respectively for two stocking densities. Highermean growth rate, specific growth rate and low FCR were witnessed only in thelow stocking density. The relationship between growth and days of culture issignificant (P0.05).Advantages of low stocking are witnessed with reference to individual body weightat the harvest.